(untitled) (Archives of Pediatrics of Uruguay, 2021)
Introduction: on March 11th, COVID-19 caused by SARS CoV-2 was declared a pandemic. The Uruguayan National Coronavirus Plan was set up on March 16th and suspended in-person educational activities and public shows; set a voluntary quarantine, social distancing, face masks and hand washing as main recommendations. The British Hospital Contingency Committee approved the healthcare modifications established by Department of Pediatrics. Objective: describe hospitalizations for acute respiratory infection (ARI) in children of 0-14 years of age between 1/1/2020 and 5/31/2020 during the pandemic, compare them to those in the same period in 2018 and 2019, and describe the microbiological findings in children with IRA and suspected cases of SARS CoV-2 infection during 2020. Methodology: we included all discharges from Moderate Care Unit due to ARI, bronchiolitis, viral pneumonia and pneumonia and described total discharges, cases and rates per 1000 discharges (Confidence Interval 95%=CI95%). In 2020, we described healthcare modifications at all levels of care (telephone or telemedicine assistance and home care was promoted) and seasonal respiratory virus cases and SARS CoV-2 nucleic acid detection results. Results: the average rate of discharges due to ARI in Moderate Care Units in 2018 and 2019 was 94 (95% CI: 72-117). In 2020, the rate was 15 (95% CI: 3-27), and showed a significant reduction of 85%. SARS CoV-2 was researched in 30 children, all results were negative. There were no hospitalizations of children of under one year of age due to influenza, RSV or SARS CoV-2 Conclusion: the measures adopted contributed to the significant reduction in hospitalizations due to ARI.